Numerical modelling of in-plane restrained concrete two-way slabs subjected to fire. (May 2021) - Wang, Yong; Wang, Gongchen; Huang, Zhaohui; Li, Lingzhi; Bu, Yixiang; Zhong, Bo; Zhang, Yajun; Ma, Shuai
Abstract: This paper presents a numerical investigation of the fire performance of eight reinforced concrete two-way slabs subjected to different in-plane restraints. A comparison of the experimental results with results predicted by a numerical model showed generally satisfactory agreement. The effects of geometric nonlinearity, or linearity, and concrete thermal strain on the fire behaviour of the tested slabs were analysed. It was found that neglecting the geometric nonlinearity led to lower predicted deflections for in-plane restrained slabs and higher predicted deflections for simply supported slabs, while a larger concrete thermal strain led to larger deflections for the concrete slabs under either restraint condition. Parametric studies were conducted to investigate the influence of in-plane restraint type, restraint level, aspect ratio, reinforcement ratio and layout, and slab thickness on the fire behaviour of the in-plane restrained slabs. The results of the parametric studies showed that the in-plane restraint type, restraint level, and aspect ratio significantly affect the deflection trends, failure mode, and fire resistance of in-plane restrained slabs. In addition, the fire-resistant performance for in-plane restrained rectangular slabs can be improved by increasing the reinforcement ratios along the short span. Highlights: The fire behaviour of eight tested concrete two-way slabs with in-plane restraint was modelled. The membrane mechanism of restrained concrete slabs in fire was analysed. The effect of several factors on the fire behaviour of restrained concrete slabs was examined. The fire resistances of restrained concrete slabs were compared based on different failure criteria.